Redo MitraClip for Late Recurrent Severe Mitral Regurgitation: Case Report and Literature Review - Goel, Sachin S. (CJC Open, 2020)
Transcatheter mitral valve repair using the MitraClip (Abbott Vascular, Santa Clara, CA) is a reasonable option for the treatment of patients with severe symptomatic degenerative mitral regurgitation (MR) who are at prohibitive surgical risk. The occurrence of recurrent severe MR after initial successful MitraClip repair is uncommon. Data are sparse on the management of recurrent severe MR after initial successful repair using the MitraClip. We describe a successful case of redo MitraClip repair for late recurrent severe MR secondary to progressive degenerative mitral valve disease after a successful initial MitraClip procedure and review the literature.